Comparative evaluation of phenolic profile and antioxidant activity of new sweet cherry (Prunus avium L.) genotypes in Turkey. Issue 4 (4th February 2022) - Ockun, Mehmet Ali; Gercek, Yusuf Can; Demirsoy, Husnu; Demirsoy, Leyla; Macit, Idris; Oz, Gul Cevahir
Abstract: Introduction: Sweet cherry ( Prunus avium L.), one of the most consumed fruits in the world, is rich in phenolic and especially anthocyanin content. Objective: The aim of this study was to evaluate the phenolic properties of 11 different sweet cherry genotypes collected from Giresun, Turkey. Methods: Total phenol, flavonoid, anthocyanin and antioxidant properties were observed spectrophotometrically in three different extraction (conventional, microwave‐assisted and ultrasound‐assisted) processes. Major phenolic, anthocyanin and antioxidant structures were visually assessed by high‐performance thin layer chromatography (HPTLC). Various phenolics in its structure were determined by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Results: T2 and E5 genotypes had the highest content in terms of total phenol, flavonoid, anthocyanin and antioxidant activity. In HPTLC, cherry samples contained high levels of chlorogenic acid, neochlorogenic acid, p ‐coumaroylquinic acid, rutin and cyanidin‐3 rutinoside. Among the phenolics examined in the LC–MS/MS method, the major compounds in the structure of cherry were found to be chlorogenic acid, rutin and catechin. The T2 genotype had higher phenolics than the other cherry samples (chlorogenic acid 19.3 mg/100 g; catechin; 3.8 mg/100 g; rutin 33.1 mg/100 g). Conclusion: As a result, T2 and E5 genotypes had higher phenolic and antioxidant activity compared to other genotypes and commercial cultivars. It can be said that the antioxidant contents of these genotypes are due to the high anthocyanin amount in their structures. In addition, T2 genotype contained more major phenolics than other cherries. In the next stage, it is recommended to carry out studies on the cultivation of these two varieties. Abstract : "Chemical profiles of different sweet cherry genotypes collected from different areas of Giresun province of Turkey were analyzed comparatively by spectrophotometric, LC‐MS/MS and HPTLC methods, and new sweet cherry samples that may have commercial potential were determined. According to the findings, T2 and E5 genotypes had better phytochemical properties than other genotypes and commercially available cultivars. In the next stage, it is recommended to carry out studies on the cultivation of these two new samples."